Creating Employee Performance Based on HR Competency, Information Technology, and Education and Training at PT. Kereta Api Indonesia - Asyari; Riomattajang; Andi Pallawagau; Muhammad Ramli (International Journal of Economics, Management, Business, and Social Science (IJEMBIS), 2026)
The aim of this research is to analyze HR competency, information technology and mentoring and training on employee performance at PT. Indonesian Railways. The research sample was carried out by random sampling with a total of 100 respondents. Data analysis test using multiple linear regression with hypothesis testing. The sample was carried out by purposive sampling with a liker scale of 100 employees. The analysis carried out includes validity tests, reliability tests, with classical assumption tests including normality test, multicollinearity test, heteroscedasticity test, T test (partial test), The results of the research found that human resource competency has a significant effect on employee performance. Information technology has a significant positive effect on employee performance, the implementation of education and training has a significant effect on employee performance.